2021
DOI: 10.5194/ms-12-539-2021
|View full text |Cite
|
Sign up to set email alerts
|

Vibroacoustic characteristics analysis of a planetary gear reducer considering the exterior housing structure

Abstract: Abstract. Previous studies have attempted to identify weak links in the dynamic characteristics of the planetary gear reducer (PGR) exterior body structure (EBS). Through numerical simulation, these studies analyzed the mode and natural frequencies and the vibration types of each order of the EBS. However, these scholars have never focused on the main factors affecting the dynamic characteristics of the EBS of this subject. This study in the topic has analyzed the vibroacoustic characteristics of an EBS and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Table 3 shows the results of the analysis of the rotational speed signal, and in the figure below the conventional reference of the width of a single band to the period of 10 signal bands. Figure 9 shows an example of the spectrum, which takes into account the mechanical parameters [9] calculated above, characterizing the operation of the BLDC motor with the gearbox [10,11]. The authors assumed that since the deflection increases, the contact area of a given tyre with the resisting surface will increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows the results of the analysis of the rotational speed signal, and in the figure below the conventional reference of the width of a single band to the period of 10 signal bands. Figure 9 shows an example of the spectrum, which takes into account the mechanical parameters [9] calculated above, characterizing the operation of the BLDC motor with the gearbox [10,11]. The authors assumed that since the deflection increases, the contact area of a given tyre with the resisting surface will increase.…”
Section: Resultsmentioning
confidence: 99%
“…The measure of the BLDC motor load during these measurements, (much like in motors controlled by the level of PWM signal filling), is the variation in the width of rotational speed signal band (Fig. 12) [11,15]. This measure was referred to changes in the tyre deflection for a specific tread pattern in order to determine the relationship between the tyre tread pattern and the generated motor load.…”
Section: Resultsmentioning
confidence: 99%
“…For the acoustic vibration coupling problem of the external body structure of the gear reducer, Jin et al [11] analyzed the vibration transmission path relationship of the external excitation point of the body, designed the results applicable to the low acoustic vibration, and optimized the parameters with the help of dynamic modification and sensitivity analysis. The results showed that the optimized design results have better dynamic response and acoustic vibration characteristics.…”
Section: Review Of Literaturementioning
confidence: 99%